Enhancing energy efficiency in zero energy buildings: Analyzing the impacts of phase change material-filled enclosures and outlet air distance on solar wall performance - Alqaed, Saeed; Mustafa, Jawed; Sajadi, S. Mohammad; Aybar, Hikmet S. (Elsevier, 2024)
This paper presents a study on solar walls integrated with phase change material (PCM) to enhance energy efficiency in zero-energy buildings. The research focuses on expanding the surface area with PCM-filled compartments to improve thermal performance. The effects of different expanded surface shapes and outlet air distances on the solar wall's temperature and PCM solidification process are investigated through numerical simulations. The findings show that semicircular surfaces with a 30 cm outlet air distance have the highest temperatures, while rectangular surfaces with the same distance have the lowest temperatures. Semicircular surfaces take the longest time to freeze PCM completely, whereas rectangular surfaces with a 30 cm gap achieve the fastest solidification. These insights provide valuable guidance for optimizing solar wall design and energy efficiency in zero -energy buildings. Finally, it was seen that by changing the shape of the extended surfaces and the air gap, the outlet air temperature changes up to 1.15 degrees and the wall temperature changes up to 1.21 degrees.
Keywords: Phase change materials; Expanded surfaces; Zero energy building; Solar wall